Nonstatistical behavior of the photoionization of spin–orbit doublets. (3rd May 2021) - Püttner, Ralph; Martins, Jessica B; Marchenko, Tatiana; Travnikova, Oksana; Guillemin, Renaud; Journel, Loïc; Ismail, Iyas; Goldsztejn, Gildas; Koulentianos, Dimitris; Céolin, Denis; Rocco, Maria Luiza Miranda; Piancastelli, Maria Novella; et al.
Abstract: The photoionization branching ratios of spin–orbit doublets are studied both experimentally and theoretically at energies several keV above threshold. The results show significant relativistic effects for Ar 2 p in the autoionizing region below the 1 s threshold, and large many-body effects for Xe 3 d and 4 d in the vicinity of the L-shell thresholds. The branching ratios in Xe are also found to vary significantly over very broad multi-keV energy regions both above and below the inner-shell thresholds. In addition, the Ar 2 p study confirms experimentally the decades-old theoretical prediction that the nonresonant branching ratio does not approach the statistical (nonrelativistic) value, and, in fact, progressively diverges from statistical with increasing photon energy.